Electrical characteristics of Pt/SrBi2Ta2O9/Ta2O5/Si using Ta2O5 as the buffer layer - Choi, HS; Kim, YT; Kim, SI; Choi, IH (INST PURE APPLIED PHYSICS, 2001)
We propose the Pt/SrBi2Ta2O9/Ta2O5/Si Structure for the application of nondestructive read-out memory. The Ta2O5 films were deposited on p-type Si (100) substrates by rf-magnetron sputtering and the SrBi2Ta2O9 films were deposited by metal organic deposition (MOD) method. Coercive field that decisively affects on the memory window becomes greater by inserting the Ta2O5 buffer layer between ferroelectric thin film and silicon substrate and thus the memory window also increases with an electric field to the SrBi2Ta2O9. The C-V characteristics of the Pt/SrBi2Ta2O9 (195 nm)/Ta2O5 (36 nm)/Si structure show memory window of 0.5-2.7 V at the applied voltage of 3-7 V. The leakage current density is 1.7 x 10(-8) A/cm(2), even at the high voltage of 10 V.
Keywords: THIN-FILMS; MEMORY